James Baldwin’s Understanding of God - Young, J. author. aut Link
XIII, 222 p.
Keywords: This book focuses on Baldwin's experiences as a gifted black writer who fought valiantly against racism and wrote openly about homosexual relationships. Baldwin's God is a 'mysteriously impersonal' force he calls love- 'something . . . like a fire, like the wind, something which can change you.'.